Productive Pinning: A Quantitative Content Analysis Determining the Use of Pinterest by Agricultural Businesses and Organizations - Jessie Topp; Scott Stebner; Lana A. Barkman; Lauri M. Baker (Journal of Applied Communications, 2014)
In recent years social media sites have experienced rapid growth among users, specifically the image-based site Pinterest. The purpose of this study was to investigate how agricultural producers and businesses were using Pinterest. A sample of 428 Pinterest users were evaluated using a quantitative content analysis to determine basic information about how Pinterest was used and the presence of four possession rituals: personalizing, claiming, sharing, and storing and hoarding. The research objectives of this study included (1) determining the number of businesses and organizations using Pinterest, (2) identifying what possession rituals are most prominently utilized by agribusinesses and agricultural organizations on Pinterest, and (3) determining what segment of the agricultural industry is represented on Pinterest the most. The results indicated agricultural producers and businesses are utilizing Pinterest but progress is still warranted. More specif ically, the results revealed agriculture’s use of Pinterest is highly personalized, with the most room for improvement being in the area of sharing content agriculturists generate themselves.
Keywords: Pinterest; social media; advocacy; possession rituals; agri-marketing